Three-dimensional mapping of cortical bone thickness in subjects with different vertical facial dimensions - Sadek, Mais Medhat; Sabet, Noha Ezat; Hassan, Islam Tarek (Progress in orthodontics, 2016)
Background The purpose of this study was to determine differences in cortical bone thickness among subjects with different vertical facial dimensions using cone beam computed tomography (CBCT). Methods From 114 pre-treatment CBCT scans, 48 scans were selected to be included in the study. CBCT-synthesized lateral cephalograms were used to categorize subjects into three groups based on their vertical skeletal pattern. Cortical bone thickness (CBT) at two vertical levels (4 and 7 mm) from the alveolar crest were measured in the entire tooth-bearing region in the maxilla and mandible. Results Significant group differences were detected with high-angle subjects having significantly narrower inter-radicular CBT at some sites as compared to average- and low-angle subjects. Conclusions Inter-radicular cortical bone is thinner in high-angle than in average- or low-angle subjects in few selected sites at the vertical height in which mini-implants are commonly inserted for orthodontic anchorage.